2016
DOI: 10.1016/j.socnet.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The embeddedness of organizational performance: Multiple Membership Multiple Classification Models for the analysis of multilevel networks

Abstract: Tranmer, M., Pallotti, F., and Lomi, A. (2016) The embeddedness of organizational performance: multiple membership multiple classification models for the analysis of multilevel networks. Social Networks, 44, There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/122367/ hospitals (higher-level, elective transfers), and between EDs and hospitals (cross-level, nonemergency transfers). Our ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Using RTM, it is possible to incorporate network data collection to random survey studies covering multiple organizations. Likewise more scholars are recognizing the need to study organization networks at multiple levels (Brass et al 2004;Zappa and Lomi, 2015;Tranmer et al, 2016), however, data collection requirements are extremely demanding for studying inter-organizational and intra-organization networks simultaneously. RTM provides a convenient approach to meet data requirements for multi level organization research as well.…”
Section: Resultsmentioning
confidence: 99%
“…Using RTM, it is possible to incorporate network data collection to random survey studies covering multiple organizations. Likewise more scholars are recognizing the need to study organization networks at multiple levels (Brass et al 2004;Zappa and Lomi, 2015;Tranmer et al, 2016), however, data collection requirements are extremely demanding for studying inter-organizational and intra-organization networks simultaneously. RTM provides a convenient approach to meet data requirements for multi level organization research as well.…”
Section: Resultsmentioning
confidence: 99%
“…That is to say, scholars are influenced by the strong social relations and reciprocity standards and have a sense of obligation to the academic community. A number of studies have shown that strong social embeddedness negatively affects the establishment of a firm's new social tie and access to information [25,26]. Secondly, scholars with higher role embeddedness are cognitively locked [27].…”
Section: Lowmentioning
confidence: 99%
“…Role embeddedness (Embed). Embeddedness itself is a concept in the social network literature, which means the behavior and institutions are constrained by ongoing social relations [26,52]. It measures the centrality of the individual in the network.…”
Section: Model Setting and Variable Definitionmentioning
confidence: 99%
“…Each level is context for the other. Statistical models helping explore the emergence and determinants of such structures are provided, for example, by Snijders and Bosker (2012), Koskinen et al (2017), Wang et al (2013Wang et al ( , 2016, Žiberna (2014), Žiberna and Lazega (2016), Zappa and Lomi (2015), Tranmer et al (2016). Today I would like to report some of our explorations of how these multilevel dynamics work, based on datasets following this linked design.…”
Section: Understanding Navigation Of Social Processes With the Analyses Of Multilevel Networkmentioning
confidence: 99%